Digital Implementation of Direct Torque Control of Induction Machines - Zuber Ahmadi, Muhd Zharif Rifqi; Jidin , Auzani; Mohamad Sapiee, Mohd Razali; Othman, Md Nazri; P.Nagarajan, Ravin Nair; JOPRI, MOHD HATTA (2013)
This paper presents a digital implementation of Direct Torque Control (DTC) for three-phase induction machine using eZdspF28335. It can be shown that the execution of DTC algorithm can be optimized by applying IQ-Math blocks which are available in MATLAB software. Applying this approach, the complex digital calculation for all mathematic operations such as multiplication, division, subtraction and etc., can be simplified and hence calculate at faster rate. It is also emphasized that the selection of Q-point that represents the fraction length of data should be appropriate in order to achieve high-degree of computational accuracy. The DTC algorithm based IQ-Math blocks was simulated and implement in real practice using eZdsp F28335 to verify its feasibility and effectiveness.